Association of atherogenic cardiac index and markers of oxidative stress in non-diabetic dyslipidemia stroke patients in a tertiary care hospital in Eastern India - Anannya Ghosh; Apratim Chatterjee; Sanchayan Sinha (Asian Journal of Medical Sciences, 2024)
Background: Stroke is a clinical syndrome consisting of rapidly developing clinical signs of focal or global disturbance of cerebral function. Antioxidants are exogenous or endogenous compounds acting by scavenging reactive oxygen species or their precursors, inhibiting reactive oxygen species formation and binding metal ions needed for the catalysis of its generation. Atherogenic index, a predictor of atherosclerosis, increases in dyslipidemia also shows a positive association with oxidative stress. Aims and Objectives: Our objective was to compare the lipid profile, the markers of lipid peroxidation (malonaldehyde and paraoxonase [PON]), and atherogenic index in non-diabetic stroke patients with healthy controls and to evaluate the correlation between the lipid parameters with markers of lipid peroxidation and atherogenic index in those patients. Materials and Methods: One hundred diagnosed stroke patients from the Neurology department were compared with 100 age-matched healthy controls. Estimation of lipid profile parameters was done by AutoAnalyzer using standardized kits. Estimation of serum malonaldehyde was done based on the principle of utilization of Thiobarbituric acid. Serum PON1 activity was estimated using paranitrophenyl acetate substrate. Results: Among the lipid profile parameters, high-density lipoprotein (HDL) was significantly lower (P<0.001) and low-density lipoprotein (LDL) was significantly higher among stroke patients. Serum malonaldehyde level was significantly increased and PON1 activity was significantly decreased in stroke patients in comparison to healthy individuals. A significant positive correlation between HDL and PON1 and a negative correlation between LDL and PON1 were found. Atherogenic index is negatively correlated with PON1. Conclusion: Low level of PON1 activity and an increased level of malonaldehyde were found in stroke patients indicating an imbalance between free radical generation and its scavenging action and also associated with more chance of atherosclerosis.